Non-Compliance Of Tun Officials Towards Ptun Decisions From The Perspective Of Fiqih Siyasah: A Case Study In Seluma Regency - Hartanto; Ismail Jalili; John Kenedi (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2025)
This study discusses the phenomenon of non-compliance of State Administrative (TUN) officials in Seluma Regency with the decisions of the State Administrative Court (PTUN) which have permanent legal force. Failure to implement PTUN decisions has a negative impact on legal certainty and reduces public trust in the justice system. This study uses a qualitative approach through a case study in Seluma Regency with in-depth interview data collection techniques and documentation studies. The results of the study indicate that the main causes of non-compliance are weak supervision, political intervention, low legal awareness of officials, and weak implementation of administrative sanctions. From the perspective of fiqh siyasah, non-compliance of officials violates the principles of justice and trust in leadership, so solutions are needed based on increasing accountability, legal education, and bureaucratic reform. The recommendations of this study include strengthening sanctions, transparency in the implementation of PTUN decisions, and socialization of fiqh siyasah values ​​in governance.